Adenine‐Driven Structural Switch from a Two‐ to Three‐Quartet DNA G‐Quadruplex - Lenarčič Živković, Martina (Angew Chem Int Ed Engl, 2018)
A G‐rich sequence found in the regulatory region of the RANKL gene, which is associated with homeostasis of bone metabolism, folds into a two‐quartet basket‐type G‐quadruplex stabilized by A⋅G⋅A and G⋅G⋅G base‐triads. Perusal of local structural features together with G/A‐to‐T modifications uncovered the critical role of A5 for the formation of a distinct antiparallel two‐quartet topology and not the three‐quartet topology that would be expected based on the sequence with four GGG‐tracts alone. The structural changes induced by the A5‐to‐T5 modification include a switch in orientation and relative positions of G‐strands that together with anti to syn reorientation of G12 provide insights into the complexity of the interactions that influence the folding of G‐rich DNA. Understanding the impact of loop residues on the stability and formation of G‐quadruplexes advances our knowledge and ability to predict structures adopted by G‐rich sequences, which are involved in regulatory mechanisms in the cell, and may also facilitate drug design.